Solve the following


xy(x3 − y3)


To find the product, we will use the distributive law in the following way:

$x y\left(x^{3}-y^{3}\right)$

$=x y \times x^{3}-x y \times y^{3}$

$=\left(x \times x^{3}\right) \times y-x \times\left(y \times y^{3}\right)$

$=x^{1+3} y-x y^{1+3}$

$=x^{4} y-x y^{4}$

Thus, the answer is $x^{4} y-x y^{4}$.



Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now